Atomically thin nonreciprocal optical isolation - Lin, Xiao (2014)
Optical isolators will play a critical role in next-generation photonic circuits, but their on-chip integration requires miniaturization with suitable nonreciprocal photonic materials. Here, we theoretically demonstrate the thinnest possible and polarization-selective nonreciprocal isolation for circularly polarized waves by using graphene monolayer under an external magnetic field. The underlying mechanism is that graphene electron velocity can be largely different for the incident wave propagating in opposite directions at cyclotron frequency, making graphene highly conductive and reflective in one propagation direction while transparent in the opposite propagation direction under an external magnetic field. When some practical loss is introduced, nonreciprocal isolation with graphene monolayer still possesses good performance in a broad bandwidth. Our work shows the first study on the extreme limit of thickness for optical isolation and provides theoretical guidance in future practical applications.